(untitled) (Journal of Science and Technology, 2016)
Professor Eric Hobsbawm may be described as a professional Marxist historian. The subjects he writes about include labour, artisans, peasants and the working class or, in short, the “forgotten majority” in the society. He regards himself as a historian of society and he practises dynamic history which is the interpretation of society with a view to changing it for the better. He has suggested that the pre-condition for history must be the existence of a total unit or system and has, accordingly, argued that world history – which he has undertaken in Age of Capital is only possible after 1848 when it became possible to think of the world as one unified economy.